COMPARATIVE ASSESSMENT OF ROAD RATING SYSTEMS - OLUFIKAYO ADERINLEWO (Journal of Engineering Studies and Research)
In this study, three road rating systems were assessed and compared after carefully applying them to five major road case studies. The essence of these rating systems is to provide a consistent, reasonably objective and systematic approach for establishing priorities and scheduling and budgeting roadway rehabilitation requirements. The effectiveness of these systems was measured during the road condition survey and compared with one another. The most effective system out of the three was determined based on the different types and severity levels of pavement distresses identified for the five different routes.